2015
DOI: 10.1096/fj.15-276527
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43 reboots meiosis and reseals blood‐testis barrier following toxicant‐mediated aspermatogenesis and barrier disruption

Abstract: Earlier studies have shown that rats treated with an acute dose of 1-(2,4-dichlorobenzyl)-1H-indazole-3-carbohydrazide (adjudin, a male contraceptive under development) causes permanent infertility due to irreversible blood-testis barrier (BTB) disruption even though the population of undifferentiated spermatogonia remains similar to normal rat testes, because spermatogonia fail to differentiate into spermatocytes to enter meiosis. Since other studies have illustrated the significance of connexin 43 (Cx43)-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 58 publications
(94 reference statements)
1
35
0
3
Order By: Relevance
“…It was shown that PFOS exerted its effects in Sertoli cells by perturbing F-actin organization in Sertoli cells, thereby disrupting localization of TJ- and basal ES-proteins at the Sertoli cell-cell interface, and associated with a disruption of the GJ-communication function based on a functional dye-transfer FRAP (fluorescence recovery after photobleaching) assay 25 . These phenotypes are somewhat similar to adjudin-induced aspermatogenesis in the testis in vivo 19 20 . We thus sought to examine if overexpression of Cx43 could rescue the PFOS-mediated Sertoli cell injury, because if it could, these findings offer the basis for therapeutic management of PFOS-induced testis injury through gene therapy by overexpressing Cx43, such as the use of nanoparticles that contain mammalian expression vector with the full-length Cx43 cDNA 26 27 28 .…”
supporting
confidence: 60%
See 2 more Smart Citations
“…It was shown that PFOS exerted its effects in Sertoli cells by perturbing F-actin organization in Sertoli cells, thereby disrupting localization of TJ- and basal ES-proteins at the Sertoli cell-cell interface, and associated with a disruption of the GJ-communication function based on a functional dye-transfer FRAP (fluorescence recovery after photobleaching) assay 25 . These phenotypes are somewhat similar to adjudin-induced aspermatogenesis in the testis in vivo 19 20 . We thus sought to examine if overexpression of Cx43 could rescue the PFOS-mediated Sertoli cell injury, because if it could, these findings offer the basis for therapeutic management of PFOS-induced testis injury through gene therapy by overexpressing Cx43, such as the use of nanoparticles that contain mammalian expression vector with the full-length Cx43 cDNA 26 27 28 .…”
supporting
confidence: 60%
“…Overexpression of Cx43 was shown to be able to re-initiate spermatogenesis by re-booting meiosis I/II in adjudin treated rats. For instance, round spermatids were detected in considerable number of tubules vs. adjudin treated rats without Cx43 overexpression in the testis 20 . Detailed analysis of tubules that displayed signs of meiosis in these adjudin treated rats has shown that besides corrective spatiotemporal expression of Cx43 in the seminiferous epithelium similar to normal rat testes, F-actin organization was re-built through proper spatiotemporal expression of actin nucleation protein formin 1 and actin barbed end capping and bundling protein Eps8 20 .…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…IF was performed using frozen cross sections of testes at 7-m in a cryostat at Ϫ22°C to visualize BTB-associated proteins, such as N-cadherin, ß-catenin, occludin and ZO-1, or actin regulatory proteins Arp3 and Eps8 (48,50). To visualize MTs (e.g., ␣-tubulin), EB1, and Dync1h1, IF was performed using 5-m thick sections of testes fixed in either modified Davidson fixative (for ␣-tubulin or EB1 staining) or Bouin's fixative (for Dync1h1 staining) and paraffin embedded, or fresh Sertoli cells cultured on coverslips (IF) as earlier described (48,50,91). Frozen sections or cells were fixed in 4% PFA or ice-cold methanol for 5-10 min (IF), permeabilized in 0.1% Triton X-100 for 5-10 min (IF).…”
Section: Introductionmentioning
confidence: 99%
“…The ORF (open reading frame) of the full-length plastin 3 cDNA clone was amplified from rat Sertoli cell cDNAs reversed transcribed from total RNAs using AccuPrime Pfx DNA polymerase (Invitrogen, Carlsbad, CA), and was cloned into the pCI-neo mammalian expression vector (Promega, Madison, WI) by PCR using the primer pair listed in Table 2, including the corresponding Mul I and Sal I restriction enzyme recognition sites as described. 30,34 This cDNA clone of 1893 bp with start and stop codons was obtained using Sertoli cells total cDNAs, and its identity was confirmed by direct nucleotide sequence analysis at Genewiz, which was identical to GenBank Accession Number: NM_031084.1 for plastin 3 except that nucleotides at 622-624 GGG encoding Gly was GGA (also encoding Gly) in this rat testis clone. The authenticity of this cDNA clone was confirmed in 4 separate cloning and sequencing experiments.…”
Section: Cloning Of Plastin 3 Into Pci-neo Mammalian Expression Vectormentioning
confidence: 73%